SALMONELLA SPP. CONTAMINATION IN CHICKEN MEAT SOLD IN MARKETS - Prawira, Putri Azahra; Wardhananti, Maya Anggi; Prihanani, Nur Ika (Buletin Veteriner Udayana; Vol. 15 No. 6 December 2023, 2023)
Chicken meat is a food of animal origin that is widely consumed by Indonesian people because it has high nutritional value. Chicken meat, as a source of animal protein, is very easily damaged because it is susceptible to contamination with pathogenic bacteria and putrefactive bacteria which can cause health problems for humans. Contamination of pathogenic bacteria in foodstuffs of animal origin needs special attention, because the increasing number of microbes such as Salmonella spp. Contaminating chicken meat can cause Salmonellosis disease in humans. This research aims to obtain an overview of the characteristics of Salmonella spp bacterial contamination. in chicken sold in traditional markets so that food safety is guaranteed and does not cause foodborne diseases. The method used in this research uses the literature review method, namely by looking for sources of scientific articles or research J.s that are relevant to the material or topic of the review. The results obtained were 141 positive samples for Salmonella spp. and 357 samples were negative for Salmonella spp. This bacterial contamination is caused by a lack of attention to hygiene in the processing, storage and distribution of chicken meat. Researchers concluded that the bacterial contamination of Salmonella spp. found in chicken meat sold in traditional markets as a cause for the quality of chicken meat to decrease so that it is not allowed for human consumption. Therefore, a strategy is needed to control Salmonella through prevention and control from farm to table.